Detection Method of Partial Discharge on Transformer and Gas-Insulated Switchgear: A Review - Faizol, Zulbirri; Zubir, Farid; Mat Saman, Norhafezaidi; Ahmad, Mohd Hafizi; A. Rahim, Mohamad Kamal; Ayop, Osman; Jusoh, Muzammil; A. Majid, Huda; Yusoff, Zubaida (Mdpi, 2023)
The detection of partial discharge (PD) activities in high-voltage equipment can be conducted according to several mechanisms of signal detection, including electromagnetic wave signal detection, acoustic signal detection, chemical reactions, electrical signal detection, and optical emission detection. Recently, multiple methods of detection and localization of partial discharge activities, which occurred in power transformers and gas-insulated switchgear (GIS), have been proposed to monitor the health condition of high-voltage equipment, especially when the awareness regarding preventive maintenance has been emphasized at the industrial level and among electrical providers. In aligning the needs of the industrial sector and the improvement of PD-detection methods, this manuscript focuses on reviewing the current practice methods for the detection and localization of PD signals in high-voltage equipment, comparing their efficacy, and summarizing the future direction of research work-related methods of PD detection. The comparative reviews are discussed in terms of the mechanism of PD signal detection, indication parameters, calibration techniques, and the advantages and limitations of each method of PD measurement in detail.